An adjustable step stool for stunted people - Haszhar, Nur Shafiqah Syuhadah; Talib, Norfazillah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Stunted people common problem is that they have difficulties to gain a job and often has low self-esteem in themselves. However, the current tools in the market which for the stunted people has fix height, expensive and the size is uncomfortable to use. Therefore, this research and development project is to create an assist tools that can adjusted the height up to 30 cm for the stunted people which will help them in working or ease them to gain a slight height, thus they can do their work properly and effectively. In addition, the tools can withstand up to a specific weight which is 150kg below. The limitation of height and weight was estimated through the average of Malaysian people height and weight. The product design was based on the design process flow chart by George E. Dieter. Prior to the development of the product, a survey was conducted to determine the requirement of the design specification. Furthermore, an analysis was conducted to determine the stress, strain, displacement, and the Factor of Safety of the tools. From the result, the value gained from the analysis was recorded to choose the best parameter that need to be used in designing the tools. The result for the whole design analysis shows that the von mises stress recorded below than the yield stress (2.206 x 103 MPa) which was 9.239x 101 MPa. Whilst, the values of strain and displacement were 2.783x 10-4 and 3.32 0x 10-1 mm respectively. Further, the factor of safety of this tool is 2.2 which is a high value that indicates the tool is safe to be use by humans. Finally, a prototype of this design was successfully fabricated to the concept of prove the screw mechanism and the function of the tools.